Samarium (III) triflate-doped chitosan electrolyte for solid state electrochromic devices - Alves, Raquel Diana Carneiro (2018)
New solid polymer electrolytes of chitosan doped with different concentrations of samarium triflate (Sm(CF3SO3)(3)) were prepared by solvent casting technique using glycerol as plasticizer and an acetic acid solution as solvent. The properties of the prepared polymer electrolytes have been studied by thermal analysis (thermogravimetric analysis - TGA and differential scanning calorimetry - DSC), X-Ray diffraction (XRD), scanning electron microscopy (SEM), polarized optical microscopy (POM), atomic force microscopy (AFM), energy-dispersive X-Ray spectroscopy (EDS), and impedance spectroscopy. The sample with 0.20 g of Sm(CF3SO3)(3) revealed the formation of a porous morphology, while other samples showed a presence of aggregates, proven by XRD analysis. The maximum conductivity values of 3.65 x 10(-7) S cm(-1) at 30 degrees C and 2.68 x 10(-5) S cm(-1) at 90 degrees C were achieved for the sample with 0.05 g of samarium salt. These maximum values increased to 1.68 x 10(-5) S cm(-1) at 30 degrees C and 3.87 x 10(-4) S cm(-1) at 90 degrees C, respectively, when the glycerol content increased from 0.25 to 0.70 g. Finally, because of this high conductivity values, the sample with higher glycerol content was tested in small electrochromic devices (ECD) that confirmed its potential for this kind of applications. (c) 2018 Elsevier Ltd. All rights reserved.